The Osteopaths' Therapeutic Approaches Questionnaire (Osteo-TAQ) - A content validity study. (September 2022) - Thomson, Oliver P.; Vaughan, Brett; Sampath, Kesava; Draper-Rodi, Jerry; Fleischmann, Michael; Cerritelli, Francesco
Abstract: Background: Osteopathy requires reliable and valid research tools to generate evidence on the different aspects of practice including how osteopaths approach the clinical care of patients. Such research will help the osteopathy profession understand its contribution to healthcare provision and communicate this to stakeholders. However, current quantitative tools to measure the different aspects of osteopathic practice are either focused on single pain conditions or developed from other health professional contexts. Aim: The Osteopaths' Therapeutic Approaches Questionnaire (Osteo-TAQ) is a novel tool developed from qualitative research and aims to measure and describe multiple dimensions of osteopaths' therapeutic approach to patient care. The aim of this study was to further develop the Osteo-TAQ to assess the content validity of the tool. Method: A modified nominal group technique (NGT) was employed to establish whether the Osteo-TAQ items were consistent with the underlying construct and to ascertain the prevalence and strength of agreement amongst the expert group panel members ( N = 11). A content validity index (CVI) was performed to obtain the evidence for the content validity for a revised version of the Osteo-TAQ. Results: Two rounds of review and feedback by an expert panel as part of the NGT resulted in the revision of 13 of the 37 candidate items and refinement of the previously published Osteo-TAQ. Item CVI scores after phase 1 ranged from 0.44 to 1.0 and agreement was reached after two rounds. Data from the expert panel supports the content validity of the revised Osteo-TAQ items based on high levels of agreement with respect to coverage of the construct being measured. Conclusion: This preliminary work to revise and refine the Osteo-TAQ resulted in a measure that is suitable for further testing as part of a validation research program. Highlights: Osteopathy requires reliable and valid research tools to generate evidence on the different aspects of practice including how practitioners approach the clinical care of patients. Such research will help the profession describe the complexity and variation of osteopaths' therapeutic approaches and understand and communicate osteopathy's contribution to healthcare provision. The Osteo-TAQ is a 36-item questionnaire developed from qualitative grounded theory research which appears to be a have good content validity and is a feasible instrument to characterise osteopaths' therapeutic approach.